Moderate Temperature Reduction Changes the High‐Light Acclimation Strategy of Lettuce Plants - Lempiäinen, Tapio; Muth‐Pawlak, Dorota; Vainonen, Julia P.; Rintamäki, Eevi; Tikkanen, Mikko; Aro, Eva‐Mari (Wiley, 2025)
In nature, environmental conditions are constantly changing, requiring plants to have numerous regulatory mechanisms to keep light harvesting and metabolism in balance. Here, we show that high light (HL) induces a much stronger non-photochemical quenching (NPQ) when lettuce plants are exposed to 1500 μmol photons m-2 s-1 for 4 h at 13°C (low temperature, LT) compared to 23°C (growth temperature, GT). GT/HL treatment induced NPQ to relax during 1 h in darkness. In contrast, LT/HL treatment induced an exceptionally high NPQ that only partially relaxed during 1 h in darkness at GT. Such a high sustained NPQ (sNPQ) cannot be explained by the canonical NPQ mechanism(s). Instead, sNPQ was associated with a transient increase in phosphorylation of minor LHCII antenna proteins, LHCB4.1/LHCB4.2 and partial disassembly of PSII-LHCII complexes. This coincided with increased expression of the light-harvesting-like proteins SEP2 and ELIP1.2, the PSII assembly proteins HCF173 and LPA3, and accumulation of the pre-D1 protein, indicating delayed PSII repair. These results lead us to propose that under LT/HL, the phosphorylation of LHCB4.1/LHCB4.2 initiates the disassembly of PSII-LHCII supercomplexes, allowing accumulated SEP2 to bind to CP47, presumably leading to quenching of the inner PSII core antenna. The free CP43 core antenna, released from PSII at an early stage of repair, is proposed to be protected by accumulated LPA3. Apparently, the cascades of regulatory mechanisms are specific to each combination of environmental changes, depending on their concomitant effects on chloroplast redox balance and PSII repair rate, with induced PSII core antenna quenching contributing to sNPQ.
Keywords: enviromental acclimation; non‐photochoemical quenching; photoinhibition; photosystem II repair; protein phosphorylation.